Illicit tobacco trade between the United States and Mexico El comercio ilícito de tabaco entre los Estados Unidos y México - John W Colledge III (Instituto Nacional de Salud Pública, 2012)
OBJECTIVE: To provide a brief history of the illicit tobacco trade between Mexico and the United States. MATERIALS AND METHODS: Research included a previously published study: "Cigarette taxes and smuggling: A statistical analysis and historical review", published by the Mackinac Center for Public Policy; US Customs and Border Protection data; various US court documents; General Accountability Office reporting; media reports; other historical material, and a personal interview. RESULTS: The research revealed that there is no credible evidence of organized criminal activity related to the illicit trade in tobacco products from Mexico into the United States. However, there is clear and convincing evidence of organized criminal activity in smuggling tobacco products from the United States into Mexico for at least 167 years. CONCLUSION: Historical records from 1845 into the 21st century clearly demonstrate that the United States was usually the source country for tobacco products moving illegally between the two countries. OBJETIVO: Describir brevemente la historia del comercio ilícito de tabaco entre Estados Unidos y México. MATERIAL Y MÉTODOS: La investigación incluye publicaciones previas, como "Impuestos sobre los cigarrillos y el contrabando: Un análisis histórico y estadístico"; datos de la Agencia de Aduanas y Protección Fronteriza; varios documentos de la Corte; los informes de la Oficina General de Rendición de Cuentas de EU; notas de prensa; materiales históricos, y una entrevista personal. RESULTADOS: La investigación reveló que no hay pruebas creíbles de actividad delictiva organizada relacionada con el comercio ilícito de productos de tabaco de México a EU. Sin embargo, hay pruebas claras y convincentes de que esta actividad se ha realizado de EU a México por lo menos durante 167 años. CONCLUSIÓN: Los registros históricos desde el año 1845 claramente demuestran que EU solía ser el país de origen del tabaco ilegal entre los dos países.